Integration of Reverse Engineering and Additive Manufacturing Methods in the Design and Development of Prosthetic Products : A Literature Review - Rumapea, Elsa S E; Ginting, Rosnani; Ishak, Aulia (Jurnal Sistem Teknik Industri, 2025)
The integration of reverse engineering (RE) and additive manufacturing (AM) in the design and development of prosthetic devices has shown significant potential for improving the customization, efficiency, and overall quality of these essential medical aids. This paper reviews recent advancements in the use of RE and AM for prosthetics, highlighting key methodologies and findings from various studies. The results demonstrate that combining these technologies can enhance mechanical properties, dimensional accuracy, and user satisfaction while reducing production costs and time. However, challenges such as material biocompatibility and the need for standardized frameworks remain. Continued research and collaboration among researchers, clinicians, and industry stakeholders are essential to fully realize the potential of RE and AM in prosthetic development, ultimately improving the quality of life for individuals with limb loss.